Comparison of Loss in Silica and Chalcogenide Negative Curvature Fibers as the Wavelength Varies - Wei, Chengli; Hu, Jonathan; Menyuk, Curtis R. (Frontiers in Physics, 2016)
We computationally study fiber loss in negative curvature fibers made with silica, As2S3 chalcogenide, and As2Se3 chalcogenide glasses with a fixed core-diameter-to-wavelength ratio of 30. We consider both simple and nested geometries as the transmission wavelength varies. At wavelengths shorter than 4.5 μm, silica negative curvature fibers have a loss that is around or below 10−1 dB/m and are preferable to chalcogenide fibers. At wavelengths longer than 4.5 μm, it is preferable to use As2S3 chalcogenide or As2Se3 chalcogenide negative curvature fibers since their loss is one or more orders of magnitude lower than the loss of silica negative curvature fibers. With nested negative curvature fibers, chalcogenide fibers have losses that are lower than those of silica fibers at wavelengths larger than 2 μm. However, it is still preferable to use silica nested negative curvature fibers at wavelengths less than 4.5 μm and with a loss around or lower than 10−1 dB/m due to the fabrication advantages of silica fibers.